Study of the factors affecting embryo yields and quality in superovulated Morada Nova ewes that underwent non-surgical uterine flushing - Oliveira, Maria Emilia Franco [UNESP]; Arrais, Aline Matos; de Mello, Marco Roberto Bourg; Vergani, Gabriel Brun [UNESP]; Figueira, Lucas Machado; Esteves, Sérgio Novita; Pereira, Verônica Schinaider do Amaral; Garcia, Alexandre Rossetto; Bartlewski, Pawel Mieczyslaw; da Fonseca, Jeferson Ferreira (Wiley, 2022)
The present study compared the outcomes of in vivo embryo production in Morada Nova ewes subjected to either 9-day (G-9SOV, n = 21) or 12-day (G-12SOV, n = 21) progesterone (P4)-based estruses synchronization protocol coupled with superovulatory treatment with decreasing doses of porcine follicle-stimulating hormone (133 mg of pFSH given over 3 days). Non-surgical embryo recovery (NSER) was performed 6–7 days after the onset of oestrus. Total antral follicle count doubled from the first to the sixth pFSH dose in both groups (p <.05). Oestrus responses did not vary between the two groups of animals (95.2%). Corpora lutea (CL) were detected in 85.0% and 60.0% of ewes that previously manifested oestrus behaviour in G-9SOV and G-12SOV respectively. NSER was successfully completed in 86.2% of ewes that had CL (p >.05). The mean number of CL per ewe/successfully flushed donor ewe was greater (p <.05) in G-12SOV (12.3 ± 1.7/12.1 ± 1.9) than in G-9SOV (7.9 ± 1.4/8.2 ± 1.6). Mean numbers of retrieved blastocysts and viable embryos were greater (p >.05) in G-12SOV (5.8 ± 1.9 and 3.7 ± 1.7) than G-9SOV (3.5 ± 1.1 and 0.8 ± 0.3 respectively). The total follicle count (all follicles ≥2 mm in diameter) at the sixth pFSH dose (at P4-device removal) was positively correlated (p <.05) with the number of CL (r =.95) and viable embryos (r =.91) in G-12SOV. The ewes with ≥10 Cl (48% of all flushed donors) yielded 80.5% of viable embryos. In summary: (a) Morada Nova ewes from G-12SOV group had better superovulatory responses compared with G-9SOV group; (b) total follicle count at the last pFSH dose was a good predictor of superovulatory responses only in the ewes primed with P4 for 12 days; and (c) animals with ≥10 ovulations are main contributors to viable embryo production in Morada Nova ewes.
Keywords: in vivo embryo production; naturalized sheep breed; non-surgical embryo recovery; NSER; superovulation